EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN “UNO SHORF” TERHADAP PELAJARAN SHORF KELAS 2 KMI DI PONDOK PESANTREN MODERN AR RIDHO SENTUL TAHUN AJARAN 2023-2024: The Effectiveness of Using "UNO Sharf" Media in Teaching Sharf Lessons for the Second Year at the Kulliyyatul Mu’allimin al Islamiyah Ar-Ridho Sentul - Fata, Khoirul; Tsani, Fadhilah Akbar Adyana; Ramadhansyah, Muhammad Faisal (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2024)
Learning media "UNO Sharf" is a learning media of small cards modified from the UNO card game as a tool used by teachers in teaching or assisting teachers in providing understanding of certain concepts in learning, especially in Shorf lessons. In the initial observation at the institution, especially during teaching and learning activities, it was still faced with various problems, which affected the students' low scores. With this problem, researchers tried to provide a solution in the form of learning media "UNO Sharf" in Sharf lesson. The research was conducted using quantitative pre-experimental methods by design and the collection of data through test. From this study, it was concluded that the results were obtained, namely variable (X) learning media "UNO Sharf" effective if applied to variable (Y) class 2 KMI Sharf Lesson at the Kulliyyatul Mu’allimin al Islamiyyah Ar-Ridho Sentul. This can be seen from the results of the analysis test using the Wilcoxon Signed Rank Test method which is intended with a significance of 0.000 < 0.050, meaning that Ho is rejected and Ha is accepted. Then the average positive rank of 25 students was 13.00. Based on valid test results, researchers suggest that the learning media "UNO Sharf" can be used as a learning medium at the Kulliyyatul Mu’allimin al Islamiyyah Ar-Ridho Sentul create a good teaching and learning atmosphere and make teachers more creative and innovative.